(untitled) (Brazilian Journal of Radiation Sciences, 2025)
This work focuses on modeling the Swedish Advanced Lead Reactor (SEALER-Artic), considering current trends in the development of Small Modular Reactors (SMRs) and the well-known advantages of lead-cooled nuclear systems. The objective of the study is to compare neutronic parameters using the following stochastic codes: Monte Carlo N-Particle, version 6.2.0 (MCNP 6.2.0), and Open Monte Carlo, version 0.14.0 (OpenMC 0.14.0). In this context, the neutron energy spectrum, the radial neutron flux profile in the reactor core, the relative power distribution, the criticality, and the fuel evolution during the burnup cycle of SEALER-Artic are evaluated. The steady-state results show good agreement of neutronic parameters between the codes. After the burnup, the final fuel composition shows a greater difference, possibly due to the nuclear data used in the decay calculation and the truncation of the atomic fraction calculation during the fuel evolution simulation.